Antioxidant Activities, Metabolic Profiling, Proximate Analysis, Mineral Nutrient Composition of Salvadora persica Fruit Unravel a Potential Functional Food and a Natural Source of Pharmaceuticals - Kumari, Asha; Parida, Asish K.; Rangani, Jaykumar; Panda, Ashok (Frontiers in Pharmacology, 2017)
Salvadora persica is a medicinally important plant mainly used in oral hygiene. However, little attention has been given towards the nutritional prominence of this plant. This study encloses the proximate and mineral nutrient contents, amino acid composition, metabolite profiling and antioxidant potential of S. persica fruit. The ripen fruit contained substantial amount of sugars, mineral nutrients, carotenoids, polyphenols and flavonoids. The metabolic profiling of the fruit extract by GC-MS revealed a total of 22 metabolites comprising of sugars, sugar alcohols, organic acids, organic base and aromatic silica compound. The identified metabolites have been previously reported to have potential antioxidant, antimicrobial, anti-hyperglycemic and antitumor properties. The GC-MS analysis indicated high glucose and glucopyranose (42.90 mg 100g-1) contents in fruit of S. persica. The fruit extract demonstrated a significantly higher antioxidant and ROS scavenging properties along with high contents of mineral nutrients and essential amino acids. HPLC analysis revealed presence of essential and non-essential amino acid required for healthy body metabolism. The cysteine was found to be in highest amount (733.69 mg 100g-1 DW) among all amino acids quantified. Specifically, compared to similar medicinal plants, previously reported as a source of non-conventional food and with some of the commercially important fruits, S. persica fruit appears to be a potential source of essential mineral nutrients, amino acids, vitamins (ascorbic acid and carotenoid) and pharmaceutically important metabolites contributing towards fulfilling the recommended daily requirement of these for a healthy human being. This is the first report establishing importance of S. persica fruit as nutraceuticals. The data presented here proposed that fruit of S. persica may be used as functional food or reinvigorating ingredient for processed food to reduce deficiency of nutrients among the vulnerable population group. The phytochemicals identified from S. persica fruit may be used as natural source for pharmaceutical preparations.